The Effect of Implementing e-Government on the Efficiency of Population Administration Services in Tangerang City - Hadyalbarr, Dhaysaq (Generasi Sains Indonesia, 2025)
This study investigates the effect of implementing e-Government on the efficiency of population administration services in Tangerang City. The research analyzes how digitalization in public administration has enhanced service delivery, streamlined processes, and improved citizen satisfaction. The results show that e-Government initiatives, such as online service platforms and digital document management, have led to reduced processing times, increased accessibility, and greater convenience for citizens. Additionally, the adoption of e-Government has fostered greater transparency and accountability in government operations. Despite these positive outcomes, the study identifies challenges related to digital literacy, infrastructure, and equitable service delivery, suggesting areas for further improvement. These findings highlight the significant potential of e-Government to enhance public administration but also emphasize the need for continuous refinement and adaptation to address emerging challenges.